Early versus delayed initiation of cytomegalovirus prophylaxis after liver transplant. Issue 8 (1st July 2022) - Magid, Mackenzie; Byrns, Jennifer; Gommer, Jennifer; Yang, Zidanyue; Lee, Hui‐Jie; Harris, Matt
Abstract: Objectives: Delaying cytomegalovirus (CMV) prophylaxis after liver transplantation may limit medication side effects and reduce inpatient drug costs. The primary objective of this study was to determine the incidence of CMV DNAemia in liver transplant recipients who initiated prophylaxis immediately after transplant (early prophylaxis) and those who initiated prophylaxis on postoperative day 7 or at discharge, whichever came first (delayed prophylaxis). Study Design: This was a retrospective, single‐center study of adult liver transplant recipients between February 2017 and February 2019. Patients who were at low risk for CMV (D−/R−), received dual organs, had a history of invasive CMV disease, or received prophylaxis with an agent other than ganciclovir/valganciclovir were excluded. Chart review of patient profiles was completed 9 months following the transplant, and the primary end point was the first positive CMV PCR within that timeframe. Cumulative incidence of CMV DNAemia was estimated by adjusting for competing events for early and delayed prophylaxis groups. The subdistribution hazard model was utilized to examine the effect of the timing of prophylaxis on CMV DNAemia while accounting for CMV serostatus. Secondary end points included peak quantifiable viral load, time to detection, and incidence of tissue‐invasive disease. Results: A total of 119 patients (60 early prophylaxis and 59 delayed prophylaxis) were included, and baseline demographics were similar except for sex. Twenty patients in the early group and 17 in the delayed group developed CMV DNAemia within 9 months of transplant with a cumulative incidence of 31.7% (95% confidence interval (CI) 20%, 44%) and 28.8% (95% CI 18%, 41%), respectively. After controlling for CMV serostatus, the relative incidence of DNAemia was similar between prophylaxis groups (subdistribution hazard ratio: 1.01, 95% CI 0.53, 1.90). Conclusions: No significant difference in CMV DNAemia within 9 months of liver transplant was observed between patients who received early and delayed prophylaxis. Future studies are warranted to conclude that delaying prophylaxis can be considered a safe alternative to initiating prophylaxis immediately after transplant.